Living on the edge: timing of Rand Flora disjunctions congruent with ongoing aridification in Africa - Pokorny, Lisa; Riina, Ricarda; Mairal, Mario; Meseguer, Andrea S.; Culshaw, Victoria; Cendoya, Jon; Serrano, Miguel; Carbajal, Rodrigo; Ortiz, Santiago; Heuertz, Myriam; Sanmartín, Isabel (Frontiers in Genetics, 2015)
The Rand Flora is a well-known floristic pattern in which unrelated plant lineages show similar disjunct distributions in the continental margins of Africa and adjacent islands —Macaronesia-northwest Africa, Horn of Africa-Southern Arabia, Eastern Africa, and Southern Africa. These lineages are now separated by environmental barriers such as the arid regions of the Sahara and Kalahari Deserts or the tropical lowlands of Central Africa. Alternative explanations for the Rand Flora pattern range from vicariance and climate-driven extinction of a widespread pan-African flora to independent dispersal events and speciation in situ. To provide a temporal framework for this pattern, we used published data from nuclear and chloroplast DNA to estimate the age of disjunction of 17 lineages that span 12 families and 9 orders of angiosperms. We further used these estimates to infer diversification rates for Rand Flora disjunct clades in relation to their higher-level encompassing lineages. Our results indicate that most disjunctions fall within the Miocene and Pliocene periods, coinciding with the onset of a major aridification trend, still ongoing, in Africa. Age of disjunctions seemed to be related to the climatic affinities of each Rand Flora lineage, with subtropical taxa dated earlier (e.g., Sideroxylon) and those with more xeric affinities (e.g., Campylanthus) diverging later. We did not find support for significant decreases in diversification rates in most groups, with the exception of older subtropical lineages (e.g., Sideroxylon, Hypericum, or Canarina), but some lineages (e.g., Cicer, Campylanthus) showed a long temporal gap between stem and crown ages, suggestive of extinction. In all, the Rand Flora pattern seems to fit the definition of biogeographic pseudocongruence, with the pattern arising at different times in response to the increasing aridity of the African continent, with interspersed periods of humidity allowing range expansions.